2020
DOI: 10.1002/ece3.7075
|View full text |Cite
|
Sign up to set email alerts
|

Insect morphometry is reproducible under average investigation standards

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Our data quality evaluations showed negligible differences when different people place landmarks, which confirms previous investigations of this aspect in other studies [ 54 , 55 ]. We could also demonstrate that the differences between forewing drawings from the literature and photographs of flattened wings were minor, at least if the former were obtained in a standardised fashion similar to the one used by Townes [ 36 38 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our data quality evaluations showed negligible differences when different people place landmarks, which confirms previous investigations of this aspect in other studies [ 54 , 55 ]. We could also demonstrate that the differences between forewing drawings from the literature and photographs of flattened wings were minor, at least if the former were obtained in a standardised fashion similar to the one used by Townes [ 36 38 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our preliminary results were promising: the software measurements showed exceptionally high agreement with the otherwise highly precise microscopic measurements. In many cases, researchers, including authors of the present paper, would have felt satisfied that the methods were similar and stopped at this point (Csősz et al, 2021 ). The lack of trait value dependence in agreement and the lack of variance changes were even more promising.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, we need to learn more about the potential benefits and costs of these new digital measuring methods compared to traditional microscopic examination of specimens in entomology. As previous studies have shown, morphometric measurements are subject to some degree of error due to factors such as the experience of the researchers performing the measurements, the magnification of the equipment, and the size of the measured characters (Csősz et al, 2021 ; Takács et al, 2016 ; Yezerinac et al, 1992 ). Such problems can be easily overcome by using software to take measurements from high‐resolution digital images.…”
Section: Introductionmentioning
confidence: 99%
“…All measurements are subject to error, therefore repeatability, i.e., the degree of agreement between pairs of observations made on the same measurand under the same conditions, i.e. made by the same observer, using the same microscope, following the same measurement protocol as defined in Csősz et al 35 , was tested before the statistic framework was created. The repeatability of the recorded size parameters was assessed via Intraclass Correlation Coefficients (ICC) on repeated measurements of 16 ant specimens using Package ICC 36 .…”
Section: Methodsmentioning
confidence: 99%